Territorialising Local Food Systems for an Agroecological Transition in Latin America - Levidow, Les; Sansolo, Davis [UNESP]; Schiavinatto, Mônica [UNESP] (My University, 2023)
An agroecological transition can enhance resilience by several means, e.g., managing ecological relationships through agroecosystems, enhancing farmers’ knowledge of natural resources, recycling those resources, maintaining biodiversity, and thus, flexibly adapting to environmental stresses. However, the hegemonic agri-food system has been continuing its capitalist transition, thereby undermining agroecological methods and deterritorialising social bonds. Facing this pervasive threat, an agroecological transition needs a greater convergence between agroecological production and a solidarity economy (economia solidaria or EcoSol in Latin America). Their convergence can be called EcoSol-agroecology, based on short food supply chains (called circuitos cortos there). These efforts develop territorial markets, generate more stable livelihoods, and thus keep producers on the land. In our study, each research team collaborated with an EcoSol-agroecology network to develop Participatory Action Research methods. The COVID-19 pandemic disrupted their circuitos cortos, stimulating creative adaptations or alternatives, alongside demands for policy support measures. These networks have regionally territorialised local initiatives, while also confronting obstacles from the hegemonic system. Although socioecological resilience often means a system’s capacity to bounce back, here it has meant bouncing forwards through new opportunities for solidaristic livelihoods and bonds. EcoSol-agroecology networks, agri-extensionists, and researchers have jointly developed such counter-hegemonic strategies, as illustrated by the case studies here.
Keywords: (re)territorialisation; diálogo de saberes; EcoSol-agroecology; hegemonic agri-food system; rural territorial development; socioecological resilience